Model for structuring competency-based education assessments for nurse practitioner students in a Doctor of Nursing Practice program - Holly R. Chitwood; Debra Hampton; Candice Falls; Julianne Z. Ewen; Leslie Scott; Elizabeth Tovar; Holly Stith; Andrew Makowski; Angela B. Grubbs; Jill M. Clemmons; Sheila D. Melander (Journal of the American Association of Nurse Practitioners, 2026)
ABSTRACT The 2021 American Association of Colleges of Nursing Essentials: Competencies for Professional Nursing Education , has required Colleges of Nursing to transition to implementation of competency-based education while redefining development and validation of competencies. It was essential for programs to structure assignments and activities with a focus on competency-based education assessments targeting end outcomes for practice-focused graduate nurse practitioner (NP) students. The purpose of this article is to provide a model for structuring competency-based assessments using an innovative, tiered approach for NP students in a Doctor of Nursing Practice program.